Greenhouse Heating Checklist - R. A. Bucklin; P. H. Jones; B. A. Barmby; D. B. McConnell; R. W. Henley (EDIS)
Heating requirements inside greenhouses are affected by outdoor climates, structure characteristics, types of heating systems, and the strategies of operation and management. A properly maintained greenhouse can reduce the energy consumption and thus contribute to energy savings. This article addresses the issues that might lower the system efficiency and provides a checklist to ensure the best performance of the system.